Modernisation and Time Preferences in Tanzania: Evidence from a Large-Scale Elicitation Exercise - D'Exelle, Ben; Van Campenhout, Bjorn; Lecoutere, Els (Informa UK Limited, 2012)
Assumptions about individual time preferences are important for explanations of poverty and development. Data from a large-scale elicitation exercise in Tanzania show significantly higher levels of impatience in urban areas than in rural areas. This result remains robust to adding controls for socio-economic differences between rural and urban areas, which possibly correlate with time preferences. We attribute this to differences in ‘modernisation’ between urban and rural areas, with modernisation leading to increased impatience. This is corroborated by the observed positive correlation between impatience and education; the latter being an important vehicle of modernisation for traditional societies in Tanzania.